A mixture for increasing intergranular bonding strength of permeable concrete and preparation method thereof
By using mixtures of dolomite, metakaolin and other materials in permeable concrete, the bonding strength and permeability of permeable concrete are improved, and the existing problems of low strength and pit grooves are solved, and better road usage effects are achieved.
Patent Information
- Application Number
- CN202311862955.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-12-29
AI Technical Summary
Due to the small amount of cement cemented materials used and the small bonding area between aggregates, permeable concrete has a lower strength. Especially under the cycle of vehicle loads, rainwater, etc., the surface layer threshing and dropping caused pits and grooves, which affected the road usage.
A mixture is used, including dolomite, metakaolin, cement, acrylate emulsions, gums, modified composite materials, water reducers, silane coupling agents and water. Through the combination of these components, the bonding strength and water permeability of permeable concrete are improved.
It significantly improves the bonding strength and permeability of permeable concrete, solves the problems of surface layer threshing and pit grooves, extends the service life of the road, and reduces construction costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sponge city building materials, and in particular to a mixture for increasing the inter-particle bonding strength of permeable concrete and a preparation method thereof. Background Art
[0002] Permeable concrete is a new type of environmentally friendly road material, which is widely used in the construction of sponge cities. Permeable concrete originated in Europe and the United States. It is a road paving material developed to alleviate the sharp decline of urban groundwater levels, protect groundwater resources, maintain ecological balance, and alleviate the urban heat island effect. It is conducive to the harmonious development of humans and the natural environment, and has special significance for urban rainwater and pollution prevention. Permeable concrete is a honeycomb structure with uniformly distributed holes, which is made by mixing single-size aggregates, cement, binders and water in a certain ratio. It has the characteristics of air permeability, water permeability and light weight. At present, permeable concrete is mostly used for sponge city garden road paving, but permeable concrete has a low strength due to the small amount of cement binder and the small bonding area between aggregates. Especially under the circulation of vehicle loads and rainwater, the surface layer threshes and drops particles, causing potholes and affecting road use.
[0003] Therefore, it is necessary to develop a permeable concrete bonding material with high bonding strength and good permeability to solve the current technical problems. Summary of the invention
[0004] In view of the current technical problems and in order to solve the problems of surface cracking and aggregate threshing caused by the low bonding strength of aggregates in sponge cities, the present invention provides a mixture for increasing the bonding strength between particles of permeable concrete. The mixture has the characteristics of high bonding strength, good permeability and light weight, can well solve the current problems, and the raw materials are environmentally friendly and pollution-free.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0007] 80-100 parts by weight of dolomite, 70-100 parts by weight of metakaolin, 100-200 parts by weight of cement, 30-50 parts by weight of acrylic emulsion, 10-15 parts by weight of gum, 5-10 parts by weight of modified composite material, 2-4 parts by weight of water reducing agent, 2-4 parts by weight of silane coupling agent and 40-70 parts by weight of water.
[0008] As a preferred solution of the present invention, the dolomite particle size is 6-9 nm; the cement is ordinary Portland cement P·O42.5.
[0009] In particular, dolomite can improve the water retention, cohesion and fluidity of cement concrete materials. Adding dolomite powder can reduce the bleeding and segregation of cement mixtures, reduce yield stress and viscosity, and increase flow rate. Dolomite powder will also react with cement hydration to form calcium aluminate, which improves the strength of cement-based materials. Cement mixed with dolomite powder will also react to form Mg-Al hydrotalcite, which further improves the strength and durability of cement-based materials and promotes the application of dolomite powder in cement materials.
[0010] As a preferred embodiment of the present invention, the metakaolin is ground and sieved metakaolin with a mesh size of 1250 meshes.
[0011] In particular, adding metakaolin to permeable concrete can significantly improve the strength of cement mortar and concrete. When the added metakaolin accounts for 5%-20% of cement, the strength of cement at all ages is higher than that of benchmark cement. Metakaolin contains water, and after chemical reaction with water in concrete, it will form a stable colloid, thereby improving the fluidity of concrete, reducing the internal friction of concrete, and making concrete have good pumpability, which is convenient for construction. The combination of metakaolin with dolomite, cement and other materials can better improve the bonding and strength of concrete materials.
[0012] As a preferred embodiment of the present invention, the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, which is produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province.
[0013] In particular, styrene-acrylate emulsion has good gelling properties in sponge city permeable concrete, which can effectively bond various materials in concrete together to form a stable structure, which helps to improve the strength and durability of concrete, enabling it to withstand large loads and external environmental influences. Styrene-acrylate emulsion also has a good reinforcing effect, which can improve the tensile and compressive strength of concrete, help prevent concrete from cracking or deforming when subjected to external forces, and ensure the stability and safety of its structure. At the same time, the excellent bonding properties of styrene-acrylate emulsion can effectively improve the anti-permeability of concrete, prevent water penetration, and extend the service life of buildings.
[0014] As a preferred embodiment of the present invention, the water reducer is a polycarboxylate water reducer. In particular, the polycarboxylate water reducer can form a layer of dispersant in the concrete, which can effectively reduce the pores and voids in the concrete, reduce the friction between water and cement particles, thereby reducing the water-cement ratio of the concrete, and can significantly improve the fluidity and pumpability of the concrete, reduce the water and cement consumption of the concrete, improve the strength and durability of the concrete, and also make the construction of the concrete more convenient and reduce the cost.
[0015] As a preferred embodiment of the present invention, the gum includes at least one of gum arabic, gum tragacanth, gum dammar, copal gum, peach gum, pectin and agar, preferably gum dammar and copal gum in a weight ratio of 1:1.
[0016] In particular, gum dammar and copal gum are both natural plant gelling agents with good adhesion and durability. When mixed with concrete, they can chemically react with cement, dolomite and other components in the concrete, forming a stable structure through the mutual connection between chemical bonds, thereby improving the bonding strength of the concrete material and thus improving the strength and durability of the concrete.
[0017] As a preferred embodiment of the present invention, the silane coupling agent includes at least one of KH-550, KH-560 and KH-570, which are purchased from Shandong Huachen New Materials Co., Ltd., and the silane coupling agent is preferably KH-560.
[0018] In particular, silane coupling agent KH-560 can react chemically with active ingredients in concrete to form chemical bonds, thereby improving the strength, durability and impermeability of concrete. Silane coupling agent KH-560 can also effectively improve the corrosion resistance and weather resistance of concrete. Under the influence of external environmental factors (such as ultraviolet rays, moisture, oxidation, etc.), concrete is prone to aging, corrosion and peeling. The use of silane coupling agent KH-560, cement, dolomite and acrylic emulsion through chemical reactions can enhance the internal structural stability of concrete and reduce the impact of the external environment on concrete, thereby extending the service life of the building, reducing the frequency of maintenance and replacement, and reducing construction costs.
[0019] The preparation method of the modified composite material comprises the following steps:
[0020] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of a surfactant, heat to 60-70° C., stir for 5-10 minutes, and obtain an ethanol suspension of clay for later use;
[0021] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 5-10 minutes, heat to 50-60°C, stir for 10-15 minutes, filter, and obtain modified lignin for standby use;
[0022] (3) Mix the modified lignin and clay ethanol suspension, stir evenly, add the coupling agent ethanol solution, heat to 70-80°C, keep stirring for 15-30 minutes, add buffer solution to adjust the pH of the solution, stir while adding, stop the reaction after the buffer solution is added, cool to room temperature, filter, dry, grind and sieve to obtain a modified composite material.
[0023] As a preferred embodiment of the present invention, in step (1), the surfactant is hexadecyltrimethylammonium bromide.
[0024] In particular, the clay is modified using the cationic surfactant hexadecyltrimethylammonium bromide. The cationic surfactant interacts with the negative charge on the surface of the clay to form ionic bonds, so that the negative charge on the surface of the clay is neutralized, thereby changing the electrical properties of the negative charge on the surface of the clay, reducing the surface tension of the clay, and improving the dispersibility and rheology of the clay.
[0025] As a preferred embodiment of the present invention, in step (3), the coupling agent is KH-560, the buffer solution is sodium hydroxide solution or potassium hydroxide solution, and the pH is adjusted to neutral.
[0026] In particular, clay is a natural silicate mineral with good adhesion and durability, and lignin is a natural high molecular polymer with good water resistance and corrosion resistance. When clay and lignin are mixed, a composite material can be formed, which not only retains the adhesion of clay, but also improves the durability and strength of lignin, and can form a concrete material with good adhesion and durability. This material can not only meet the strength requirements of permeable concrete, but also improve its water resistance and durability. The modified composite material formed by mixing clay and lignin can effectively improve the strength of concrete, and the modified composite material has good durability, can resist erosion from various natural environments, and the water resistance will also be relatively improved, which can effectively prevent moisture from damaging the concrete structure, further improving the durability of the concrete.
[0027] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0028] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 10-30 minutes to obtain a mixture 1;
[0029] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 10-20 minutes to obtain a mixed material 2;
[0030] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix evenly, heat to 70-80° C., keep stirring for 30-50 minutes, and obtain a mixed material.
[0031] Technical effects of the present invention:
[0032] (1) The present invention uses small-particle dolomite, 1250-mesh metakaolin and silicate cement as the main base materials. Dolomite, cement and metakaolin can react with each other. Dolomite and cement hydrate to generate calcium aluminate, which improves the strength of cement-based materials. Cement mixed with dolomite will also react to generate Mg-Al hydrotalcite, which further improves the strength and durability of cement-based materials and promotes the application of dolomite powder in cement materials. Metakaolin contains water, which will form a stable colloid after chemical reaction with cement in concrete, thereby improving the fluidity of concrete, reducing the internal friction of concrete, making the concrete have good pumpability, and improving construction efficiency.
[0033] (2) Compared with the prior art, the present invention uses clay-modified lignin as a composite material, and adds styrene-acrylate emulsion and gum with good adhesion and compatibility. Both dammar gum and copal gum are natural plant gelling agents with good adhesion and durability. When mixed with concrete, they can react chemically with cement, dolomite and other components in the concrete, and form a stable structure through the mutual connection between chemical bonds, which can improve the tensile strength and compressive strength of the concrete. The modified composite material is combined with gum and styrene-acrylate emulsion. Under the synergistic effect of water reducer and silane coupling agent, the prepared mixture can not only meet the strength requirements of permeable concrete, but also improve its waterproof performance and durability, which helps to prevent the concrete from cracking or deforming when subjected to external forces, ensures the stability and safety of its structure, improves the bonding strength of concrete materials, and thus improves the strength and durability of concrete. DETAILED DESCRIPTION
[0034] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, features and effects of the present invention are described in detail below in conjunction with the embodiments. The reagents and materials used in the present invention can be purchased from the market or prepared synthetically.
[0035] Example 1
[0036] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0037] 80 parts by weight of dolomite, 70 parts by weight of metakaolin, 100 parts by weight of cement, 30 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 40 parts by weight of water.
[0038] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0039] The preparation method of the modified composite material comprises the following steps:
[0040] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0041] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0042] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0043] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0044] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0045] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a blender and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0046] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0047] Example 2
[0048] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0049] 85 parts by weight of dolomite, 80 parts by weight of metakaolin, 120 parts by weight of cement, 35 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 45 parts by weight of water.
[0050] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0051] The preparation method of the modified composite material comprises the following steps:
[0052] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0053] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0054] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0055] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0056] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0057] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a blender and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0058] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0059] Example 3
[0060] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0061] 90 parts by weight of dolomite, 90 parts by weight of metakaolin, 150 parts by weight of cement, 40 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducing agent, 2.5 parts by weight of silane coupling agent, and 50 parts by weight of water.
[0062] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0063] The preparation method of the modified composite material comprises the following steps:
[0064] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0065] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0066] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0067] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0068] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0069] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0070] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0071] Example 4
[0072] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0073] 100 parts by weight of dolomite, 100 parts by weight of metakaolin, 180 parts by weight of cement, 50 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 65 parts by weight of water.
[0074] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0075] The preparation method of the modified composite material comprises the following steps:
[0076] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0077] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0078] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0079] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0080] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0081] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0082] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0083] Example 5
[0084] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0085] 90 parts by weight of dolomite, 100 parts by weight of metakaolin, 150 parts by weight of cement, 50 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 65 parts by weight of water.
[0086] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0087] The preparation method of the modified composite material comprises the following steps:
[0088] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0089] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0090] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0091] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0092] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0093] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0094] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0095] Example 6
[0096] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0097] 100 parts by weight of dolomite, 80 parts by weight of metakaolin, 150 parts by weight of cement, 50 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 65 parts by weight of water.
[0098] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0099] The preparation method of the modified composite material comprises the following steps:
[0100] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0101] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0102] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0103] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0104] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0105] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0106] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0107] Example 7
[0108] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0109] 80 parts by weight of dolomite, 100 parts by weight of metakaolin, 150 parts by weight of cement, 50 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 65 parts by weight of water.
[0110] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0111] The preparation method of the modified composite material comprises the following steps:
[0112] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0113] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0114] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0115] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0116] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0117] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a blender and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0118] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0119] Example 8
[0120] A mixture for increasing the intergranular bonding strength of permeable concrete, the mixture comprising the following raw materials in parts by weight:
[0121] 80 parts by weight of dolomite, 100 parts by weight of metakaolin, 120 parts by weight of cement, 30 parts by weight of acrylic emulsion, 15 parts by weight of gum, 10 parts by weight of modified composite material, 3 parts by weight of water reducer, 2.5 parts by weight of silane coupling agent, and 65 parts by weight of water.
[0122] Among them, the dolomite particle size is 7nm; the cement adopts ordinary silicate cement P·O42.5; the kaolin is ground and sieved kaolin with a mesh size of 1250 mesh; the water reducer is a polycarboxylic acid water reducer; the acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%, produced by Jinyoulai Industry and Trade Co., Ltd. in Dongying City, Shandong Province; the silane coupling agent is preferably KH-560, purchased from Shandong Huachen New Materials Co., Ltd.; the gum is composed of damara gum and copal gum in a weight ratio of 1:1.
[0123] The preparation method of the modified composite material comprises the following steps:
[0124] (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of surfactant hexadecyltrimethylammonium bromide, heat to 70° C., stir for 10 minutes, and obtain an ethanol suspension of clay for standby use;
[0125] (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 10 minutes, heat to 50°C, stir for 15 minutes, filter, and obtain modified lignin for standby use;
[0126] (3) The modified lignin and clay ethanol suspensions were mixed and stirred evenly, and the ethanol solution of coupling agent KH-560 was added, and the mixture was heated to 80°C and stirred for 30 minutes. Sodium hydroxide solution was added to adjust the pH of the solution to neutral while stirring. After the buffer solution was added, the reaction was stopped, and the mixture was cooled to room temperature, filtered, dried, ground and sieved to obtain a modified composite material.
[0127] A method for preparing a mixture for increasing the inter-particle bonding strength of permeable concrete, the method comprising the following steps:
[0128] S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 20 minutes to obtain a mixture 1;
[0129] S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 15 minutes to obtain a mixed material 2;
[0130] S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix well, heat to 80° C., and keep stirring for 45 minutes to obtain a mixed material.
[0131] Comparative Example 1
[0132] Compared with Example 3, the difference of Comparative Example 1 is that the metakaolin in Comparative Example 1 is replaced by ordinary kaolin.
[0133] Comparative Example 2
[0134] Compared with Example 3, the difference of Comparative Example 2 is that the gum in Comparative Example 2 is Dama gum.
[0135] Comparative Example 3
[0136] Compared with Example 3, the difference of Comparative Example 3 is that the gum in Comparative Example 3 is copal gum.
[0137] Comparative Example 4
[0138] Compared with Example 3, the difference of Comparative Example 4 is that no gum is added in Comparative Example 4.
[0139] Comparative Example 5
[0140] Compared with Example 3, the difference of Comparative Example 5 is that the modified composite material in Comparative Example 5 is replaced by modified lignin.
[0141] Comparative Example 6
[0142] Compared with Example 3, the difference of Comparative Example 6 is that the modified composite material in Comparative Example 6 is replaced by lignin.
[0143] Comparative Example 7
[0144] Compared with Example 3, the difference of Comparative Example 7 is that the modified composite material in Comparative Example 7 is replaced by surface-modified clay.
[0145] Comparative Example 8
[0146] Compared with Example 3, the difference of Comparative Example 8 is that the modified composite material in Comparative Example 8 is replaced by ordinary clay.
[0147] Comparative Example 9
[0148] Compared with Example 3, the difference of Comparative Example 9 is that no modified composite material is added in Comparative Example 9.
[0149] The mixed materials prepared in all the embodiments and comparative examples were tested for compressive strength, tensile strength and water permeability coefficient according to the Technical Specification for Permeable Cement Concrete Pavement CJJ / T 135-2009 standard, and all the test results are recorded in the following Table 1.
[0150] Table 1 Performance test results of mixed materials of embodiments and comparative examples
[0151]
[0152] According to the data in Table 1, the comprehensive performance of the mixed material is improved by increasing the component content in the examples, and the comprehensive performance of Examples 4-6 is better than that of other examples. However, in the comparative example, the material components are changed. When no modified composite material is added or a single gum is used, the comprehensive performance of the mixture will be greatly reduced.
[0153] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A mixture for increasing the intergranular bonding strength of permeable concrete, characterized in that: The mixture comprises the following raw materials in parts by weight: 80-100 parts by weight of dolomite, 70-100 parts by weight of metakaolin, 100-200 parts by weight of cement, 30-50 parts by weight of acrylic emulsion, 10-15 parts by weight of gum, 5-10 parts by weight of modified composite material, 2-4 parts by weight of water reducer, 2-4 parts by weight of silane coupling agent, and 40-70 parts by weight of water; The preparation method of the modified composite material comprises the following steps: (1) Weigh clay according to weight, clean and dry it, then add an ethanol solution of a surfactant, heat to 60-70° C., stir for 5-10 minutes, and obtain an ethanol suspension of clay for later use; (2) Weigh lignin according to weight, add it to nitric acid solution, shake for 5-10 minutes, heat to 50-60°C, stir for 10-15 minutes, filter, and obtain modified lignin for standby use; (3) Mix the modified lignin and clay ethanol suspension, stir evenly, add the coupling agent ethanol solution, heat to 70-80°C, keep stirring for 15-30 minutes, add buffer solution to adjust the pH of the solution, stir while adding, stop the reaction after the buffer solution is added, cool to room temperature, filter, dry, grind and sieve to obtain a modified composite material.
2. The mixture for increasing the intergranular bonding strength of permeable concrete according to claim 1, characterized in that: The metakaolin is ground and sieved metakaolin with a mesh size of 1250 meshes.
3. The mixture for increasing the intergranular bonding strength of permeable concrete according to claim 1, characterized in that: The cement used is ordinary Portland cement P·O42.
5.
4. The mixture for increasing the intergranular bonding strength of permeable concrete according to claim 1, characterized in that: The acrylic emulsion is a styrene-acrylate emulsion with a solid content of 51%.
5. The mixture for increasing the intergranular bonding strength of permeable concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
6. The mixture for increasing the intergranular bonding strength of permeable concrete according to claim 1, characterized in that: The gum includes at least one of gum arabic, gum tragacanth, gum dammar, gum copal, peach gum, pectin and agar.
7. The mixture for increasing the intergranular bonding strength of permeable concrete according to claim 1, characterized in that: The silane coupling agent includes at least one of KH-550, KH-560 and KH-570.
8. A method for preparing a mixture for increasing intergranular bonding strength of permeable concrete according to any one of claims 1 to 7, characterized in that: The preparation method of the mixed material comprises the following steps: S1. Add dolomite, metakaolin, cement and gum into a mixer by weight, mix well, and stir at room temperature for 10-30 minutes to obtain a mixture 1; S2, adding the modified composite material, acrylic emulsion and water reducing agent into a mixer and mixing them evenly, stirring at room temperature for 10-20 minutes to obtain a mixed material 2; S3. Mix the mixed material 1 and the mixed material 2, add the silane coupling agent and water, mix evenly, heat to 70-80° C., keep stirring for 30-50 minutes, and obtain a mixed material.
Citation Information
Patent Citations
Long-life permeable concrete and production method thereof
CN106348691A
Geopolymer-based pervious concrete material and preparation method thereof
CN116589248A
KR1019057440000B1